KINETIC MODELING APPROACH TO IN VIVO INTERACTIONS OF CURCUMIN AND CURCUMINOID-PIPERINE MIXTURE WITH QUETIAPINE - CIOCOTIȘAN, Iulia Maria; MUNTEAN, Dana Maria; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2025)
This study aimed to develop kinetic models that describe the preclinical drug interaction data between quetiapine, an atypical antipsychotic, and bioactive compounds derived from turmeric rhizome. The potential risk of interaction between these substances could alter the disposition of quetiapine and impact its efficacy. During the development of the kinetic models, first-order kinetic processes were assumed, and several hypotheses were evaluated, including the number of compartments for distribution, the presence of lag time in quetiapine absorption, the presystemic formation of its metabolite, and the relative bioavailability between the study groups. The most accurate models suggest that interactions between quetiapine and curcumin occur primarily at the intestinal level, as the systemic metabolism constant remained unaltered. Conversely, coadministration with curcuminoids and piperine markedly affected systemic metabolism, likely due to hepatic enzyme inhibition, resulting in a 59.6% increase in the relative bioavailability of quetiapine. The developed models successfully integrated data for quetiapine and norquetiapine, both as standalone administration and in combination with curcumin or curcuminoid-piperine bioactive compounds, capturing their disposition within the framework of pharmacokinetic interactions.